2019
DOI: 10.1007/s00127-019-01710-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in income-related inequalities of depression prevalence in China: a longitudinal, population study

Abstract: Purpose This study aimed to measure the income-related inequality of depressive symptoms and its trends among middleaged and elderly people in China. Methods Data were extracted from the 2011 baseline and 2015 follow-up of the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative survey for people aged 45 years and more. Depressive symptoms were evaluated with the Chinese version of the ten-item Center for Epidemiologic Studies Depression Scale. Five relative income levels were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…Cataract surgery was categorized as “yes” or “no” based on whether participants have obtained a cataract surgery ever. Annual household expenditure measured by food, entertainment, education, clothing, heating, traveling, fitness expenditures, taxes and donations costs, was used as a proxy for household economic status 39,40 . PCE was categorized into tertiles.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataract surgery was categorized as “yes” or “no” based on whether participants have obtained a cataract surgery ever. Annual household expenditure measured by food, entertainment, education, clothing, heating, traveling, fitness expenditures, taxes and donations costs, was used as a proxy for household economic status 39,40 . PCE was categorized into tertiles.…”
Section: Methodsmentioning
confidence: 99%
“…Annual household expenditure measured by food, entertainment, education, clothing, heating, traveling, fitness expenditures, taxes and donations costs, was used as a proxy for household economic status. 39,40 PCE was categorized into tertiles. Current smoking status and alcohol consumption were both categorized as "yes" or "no" based on whether participants smoked or drank any alcohol in the last year.…”
Section: Covariatesmentioning
confidence: 99%
“…As Zeng and Jian reported [43], the prevalence of depression can be directly and indirectly affected by socio-economic status and inequality among different residential locations in China. Our study also found relationships between monthly household income, residential location, and CR with depression.…”
Section: Factors Associated With Reduced Crmentioning
confidence: 98%
“…As Zeng and Jian reported [42], the prevalence of depression can be directly and indirectly affected by socio-economic status and inequality among different residential locations in China. Our study also found relationships between monthly household income, residential location, and CR with depression.…”
Section: Factors Associated With Reduced Crmentioning
confidence: 98%